New software to standardize the assessment of embolization of cerebral arteriovenous malformations - Г. С. Сергеев; К. Ю. Орлов; А. Л. Кривошапкин; В. П. Курбатов; М. Е. Амелин; Д. В. Чебыкин; В. А. Панарин; Л. Е. Кальнеус (Патология кровообращения и кардиохирургия, 2015)
Staged embolization of high-grade Spetzler-Martin AVMs gains popularity. The assessment of AVM devascularization degree depends on a specialist's personal experience and is very subjective. The goal of our study was to develop software for accurate and objective calculation of AVM devascularization percentage. 34 patients underwent a partial AVM embolization procedure using both adhesive and non-adhesive embolic material. Their pre- and postoperative DICOM angiographic images were assessed by both 4 skilled interventional radiologists and by our new software. We compared the evaluations of AVM devascularization degree made by the software and the specialists. 54 tests were performed. The software was based on a LabVIEW tm platform. The degree of AVM devascularization was estimated in percent values. Mean difference of values was 14,8% 1,6 (range 0%-40%) between human estimations and 3,4% 0,4 (range 0,7-9,2%) between computer calculations. Reliability of the samples was estimated by Kolmogorov-Smirnov criterion. Critical value of the criterion was 2 = 4,89, which corresponds to p value < 0,01. The new software demonstrated adequate efficiency and accuracy to be used for standardization of AVM devascularization degree evaluation.